Infants of mothers with higher physiological stress show alterations in brain function. Issue 6 (13th May 2020) - Troller‐Renfree, Sonya V.; Brito, Natalie H.; Desai, Pooja M.; Leon‐Santos, Ana G.; Wiltshire, Cynthia A.; Motton, Summer N.; Meyer, Jerrold S.; Isler, Joseph; Fifer, William P.; Noble, Kimberly G.
Abstract: Chronic stress has been increasingly linked with aberrations in children's behavioral, cognitive, and social development, yet the effect of chronic physiological stress on neural development during the first year of life is largely unknown. The present study aims to link a physiological index of chronic stress (maternal hair cortisol concentration) to maturational differences in infant functional brain development during the first year of life. Participants were 94 mother‐infant dyads. To index chronic physiological stress, maternal hair samples were assayed for the previous three months' cortisol output. To examine the development of brain function during the first year of life, six‐to‐twelve‐month‐old infants ( N = 94) completed a resting electroencephalography (EEG) recording. Infants of mothers with evidence of higher physiological stress showed increased relative low‐frequency (theta) power and reduced relative high‐frequency (alpha, high‐gamma) power, compared to infants of mothers with evidence of low physiological stress. This pattern of findings is consistent with other studies suggesting that early life stress may lead to alterations in patterns of infant brain development. These findings are important given that maturational lags in brain development can be long‐lasting and are associated with deficits in cognitive and emotional development. The present research also suggests that reducing maternal physiological stress may be a useful target for future interventions aiming to foster neurodevelopment during the first year of life. Abstract : Infants of mothers with evidence of higher physiological stress showed increased relative low‐frequency (theta) power and reduced relative high‐frequency (alpha, high‐gamma) power, compared to infants of mothers with evidence of low physiological stress. These findings are consistent with a maturational lag in brain development. Maturational lags can be long‐lasting and are associated with deficits in cognitive and emotional development.